2021
DOI: 10.5006/3963
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion in Tinplate Cans Used for Food Storage, Part 3: Effects of Cysteine, NaCl, and Tomatoes on Corrosion of Tin, Iron, and Tinplate

Abstract: Tinplate cans used to contain foodstuff are fabricated from steel coated with a thin layer of tin and then overcoated with a thin polymeric layer. Previous papers in this series investigated the corrosion behavior of tinplate cans containing chopped tomatoes or one of the chemical components found in cans of chopped tomatoes. The amino acid cysteine was found to be an aggressive agent that can cause corrosion and blackening of the can headspace region. In this study, the corrosion phenomena associated with tin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The treatment selects the microbial flora from a small group of indicator bacteria (Casolari, 1991; Chapin et al., 2014; Martin et al., 2016; Vicini, 1984) such as lactic and enterobacteria, Bacillus coagulans , butyric clostridia, and thermophilic clostridia, as well as yeasts and molds (Daryaei et al., 2013; Previdi & Previdi, 1991; Riccardi, 2001; Vicini & Zimmermann et al., 2013). This in turn influences the choice and type of container since all acidic or acidified food preserves, such as those based on tomatoes, have the property of corroding the container (Barbieri et al1971; Chang, 2021; Chang et al., 2022; Dhuey, 2019; Montanari, 2015; Palmieri et al., 2002; 2004).…”
Section: Critical Aspects In the Industrial Production Of Canned Toma...mentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment selects the microbial flora from a small group of indicator bacteria (Casolari, 1991; Chapin et al., 2014; Martin et al., 2016; Vicini, 1984) such as lactic and enterobacteria, Bacillus coagulans , butyric clostridia, and thermophilic clostridia, as well as yeasts and molds (Daryaei et al., 2013; Previdi & Previdi, 1991; Riccardi, 2001; Vicini & Zimmermann et al., 2013). This in turn influences the choice and type of container since all acidic or acidified food preserves, such as those based on tomatoes, have the property of corroding the container (Barbieri et al1971; Chang, 2021; Chang et al., 2022; Dhuey, 2019; Montanari, 2015; Palmieri et al., 2002; 2004).…”
Section: Critical Aspects In the Industrial Production Of Canned Toma...mentioning
confidence: 99%
“…and high aggressiveness (sauerkraut, asparagus). This is due to the presence of sulfur compounds, some of which, such as the amino acid cysteine, are also present in tomatoes (Chang et al., 2022), or of sulfoprotein compounds such as those present in fish products, meats, legumes, and also in corn to mask the marbling that forms on traditional tinplate (Barbieri & Rosso, 1990; Montanari, 2015). For these reasons, the use of coated cans has been continuously increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Kontominas et al [ 14 ] conducted research on common defects in the interior walls of metal cans containing tuna in soybean oil and found that lacquer adhesion failure caused by sulfides from fish allowed acidic compounds in the containers to migrate towards the internal metal surface, and this initiated discoloration and corrosion. Black deposits are sometimes observed on the internal walls of defective cans that contain sulfur-rich products [ 3 , 15 ]. These black deposits are defined as “sulfur staining,” which develops when FeS clusters form inside the defective cans [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have utilized various analytical techniques to investigate the surface layer of commercial tinplate [6][7][8][9][10] . For instance, in addition to the XPS method with argon ion sputtering used by Chen et al [11] , Sun et al [12] , and Azzerri et al [13] , other studies have employed techniques such as Raman spectroscopy [14] , atomic force microscopy [15] , and X-ray diffraction [16] to analyze the surface composition and structure of tinplate.…”
Section: Introductionmentioning
confidence: 99%